Bridging PCR: An Efficient and Reliable Scheme Implemented for Genome-Walking - Zhiyu Lin; Cheng Wei; Jinfeng Pei; Haixing Li (Current Issues in Molecular Biology, 2023)
The efficacy of the available genome-walking methods is restricted by low specificity, high background, or composite operations. We herein conceived bridging PCR, an efficient genome-walking approach. Three primers with random sequences, inner walker primer (IWP), bridging primer (BP), and outer walker primer (OWP), are involved in bridging PCR. The BP is fabricated by splicing OWP to the 5′-end of IWP’s 5′-part. A bridging PCR set is constituted by three rounds of amplification reactions, sequentially performed by IWP, BP plus OWP, and OWP, respectively pairing with three nested sequence-specific primers (SSP). A non-target product arising from IWP alone undergoes end-lengthening mediated by BP. This modified non-target product is a preferentially formed hairpin between the lengthened ends, instead of binding with shorter OWP. Meanwhile, a non-target product, triggered by SSP alone or SSP plus IWP, is removed by nested SSP. As a result, only the target DNA is accumulated. The efficacy of bridging PCR was validated by walking the gadA/R genes of Levilactobacillus brevis CD0817 and the hyg gene of rice.